A definition and set of principles for responsible consumption of gambling. Issue 3 (2nd September 2018) - Hing, Nerilee; Russell, Alex M.T.; Hronis, Anastasia
ABSTRACT: Responsible consumption of gambling (RCG) is now a major paradigm driving industry, government and public health measures that aim to prevent or minimize gambling-related harm. This is reflected in the pervasive message to 'gamble responsibly'. However, few attempts have been made to define the concept or identify its foundation principles, resulting in substantial ambiguity over what RCG means and its essential characteristics. This study addresses this void by synthesizing findings from a systematic literature review, website analysis and online survey of 107 experts – to develop a set of underlying principles and a definition of RCG. These tasks were facilitated by the reasonably consistent principles found to underpin RCG in the three data sources, despite wide variations in how the construct has previously been defined. Thus, the set of principles of RCG developed in this study (affordability, balance, informed choice, control, enjoyment, harm-free) should attract wide acceptance, as should the definition given that it combines and summarizes these principles. Adopting a consistent definition and set of RCG principles will provide a basis for developing consistent guidelines for consumers, offer direction for public health efforts for gambling harm minimization, and inform government policies and industry measures aiming to support safe gambling.